(untitled) - Brice, James C. (Boston, 2001)
Utilizing actual case studies and field photographs, this successful lab manual covers the full spectrum of historical geology sediments, plate tectonics, paleontology, and petrology in flexible, self-contained units. This manual has been developed for use in both nonmajors and combined courses in historical geology. The exercises emphasize the principles and methods by which geologists discover the origins and changing nature of our planet.
Keywords: Earth sciences,Lịch sử địa chất,Historical geology,Khoa học trái đất